2021
DOI: 10.3390/cells10102612
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculate Allocation and Sperm Characteristics Differ among Alternative Male Types in a Species of Fish with Cooperation and Competition among Unrelated Males

Abstract: Sexual selection arising from sperm competition has driven the evolution of immense variation in ejaculate allocation and sperm characteristics not only among species, but also among males within a species. One question that has received little attention is how cooperation among males affects these patterns. Here we ask how male alternative reproductive types differ in testes size, ejaculate production, and sperm morphology in the ocellated wrasse, a marine fish in which unrelated males cooperate and compete d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Alternatively, there might be a trade‐off between sperm concentration and sperm quality, as L. planeri males may strongly invest in sperm numbers at the cost of a lower sperm quality (Snook, 2005 ). A trade‐off may also occur between sperm velocity and sperm morphology as observed in ocellated wrasses where sneaker males have sperm cells with larger heads than satellite or nesting males and their sperm are also slower (Alonzo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, there might be a trade‐off between sperm concentration and sperm quality, as L. planeri males may strongly invest in sperm numbers at the cost of a lower sperm quality (Snook, 2005 ). A trade‐off may also occur between sperm velocity and sperm morphology as observed in ocellated wrasses where sneaker males have sperm cells with larger heads than satellite or nesting males and their sperm are also slower (Alonzo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm longevity could influence fertilization success notably when gamete release by males and females is not synchronous (Staponkus & Kesminas, 2014 ). In addition, the morphology of sperm could also be compared between L. fluviatilis and L. planeri as it might influence sperm velocity and siring success (Alonzo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other fish species, differences in sperm shape can be found between male morphs. For example, in the ocellated wrasse ( Symphodus ocellatus ), sneaker males had larger sperm heads, compared with nesting males and satellite males, while tail length did not differ between the three types of males (Alonzo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the role of paternal care in the evolution of testes size have reported contrasting results; that is, negative covariation in some taxa (e.g. birds [ 20 ], mammals [ 21 ] or fish [ 42 ]), a positive correlation in others (e.g. cuckoos [ 43 ]) or no association (e.g.…”
Section: Introductionmentioning
confidence: 99%